Counselling treatment versus counselling associated with jaw exercises in patients with disc displacement with reduction-a single-blinded, randomized, controlled clinical trial - Carolina Antunes Santa Cecília Simões; Mayara Aparecida Moreira da Silva; Rafael Alvim Magesty; Saulo Gabriel Moreira Falci; Dhelfeson Willya Douglas-; Patricia Furtado Gonçalves; Olga Dumont Flecha (BMC, 2023)
Abstract Objective To compare effectiveness of counselling program versus counselling program plus jaw exercises to reduce pain and click in patients with temporomandibular joint disc displacement with reduction (DDWR). Materials and methods Patients were divided into two groups: instructions for temporomandibular disorders (TMD) plus jaw exercises (test, n = 34), only TMD instructions (control, n = 34). Pain was analyzed by palpation (RDC/TMD). It was investigated if the click caused discomfort. Both groups were evaluated at baseline, 24 h, 7 days, and 30 days' post treatment. Results The click was present in 85.7% (n = 60). In 30-day evaluation, there was a statistically significant difference between groups in the right median temporal muscle (p = 0.041); and there was a statistically significant difference in treatment self-perception (p = 0.002) and click's discomfort (p < 0.001). Conclusion The exercise with recommendations showed better results, resolution of the click, and self-perception of the treatment effectiveness. Clinical relevance This study presents therapeutic approaches that are easy to perform and that can be monitored remotely. In view of the current stage of the global pandemic, these treatment options become even more valid and useful. Clinical trial register This clinical trial was registered at Brazilian Clinical Trials Registry (ReBec) under protocol RBR-7t6ycp ( http://www.ensaiosclinicos.gov.br/rg/RBR-7t6ycp/ ), Date of registration: 26/06/2020.